Os verbos ter e haver com sentido de existir em notícias de jornais da cidade de Uberaba - MG - Moreira, Éricka Fernanda Caixeta (2016)
Several researchers at different times and corpus of spoken and written modalities of Portuguese, addressed the jobs of "ter" and "haver" with meaning to “exist”, such as Callou and Avelar (2010), Almeida and Callou (2003), Avelar (2005), and others. In this work, following the Theory of Linguistics Variations by Labov, Sociolinguistics Parametric and postulates by Weinreich, Labov and Herzog of linguistic change, the overall objective was to perform a descriptive and quantitative study about the use of the verb "ter" and "haver" with the meaning of “exist” in news from the newspapers of Uberaba at the beginning of the XX and XXI centuries. We seek to observe in these two synchronicities the occurrence of variation in the use of these verbs and what linguistic and extralinguistic factors influenced in their uses. In addition, we present how the verbs "ter" and "haver" are covered in the Traditional Grammar, by Said Ali (1957), Dias (1970), Bechara (2009), and others. The corpus consisted of 300 events, wherein 150 were at the XX century and 150 at the XXI century. For quantification of the data, we submitted the occurrences to the GOLDVARB 2001 program. After analysis of data, we concluded that, in the twentieth century, we have obtained higher percentage of the verb "haver" rather than the verb "ter" (81,3% and 18,7%, respectively) and in the XXI century, there was higher frequency of the verb "haver" rather than the verb “ter" (56,7% and 43,3%, respectively), but what is important is the increased frequency of the verb “ter”. The groups of factors placed on partial analysis and at intersections, the independent variables that did most relevant were: object [-animado], “present tense”, postponed object and concrete object.